Seasonal Variations in Ion Density, Ion Temperature, and Migrating Tides in the Topside Ionosphere Revealed by ICON/IVM - Zheng Ma; Yun Gong; Shaodong Zhang; Jiaxin Bao; Song Yin; Qihou Zhou (Remote Sensing, 2023)
Based on the plasma parameters measured by the Ion Velocity Meter (IVM) instrument on the Ionospheric Connection Explorer (ICON) satellite from 2020 to 2021, we present an analysis of seasonal variations in ion density, ion temperature, and migrating tides in the low-latitude topside ionosphere. The interannual variations in total ion density and O+ density are directly impacted by solar radiation. However, the concentration of H+ is not highly related to solar activity. The measurements show that the hemispheric dividing latitude for the seasonal variation in Ti is at about 9°N. We suggest that the reason for the hemispheric dividing latitude being 9°N is because measurements at this geographical latitude represent the closest match to the geomagnetic equator. An anticorrelation in the seasonal variations between the total ion density (as well as the O+ density) and the ion temperature is observed at all observed latitudes while the correlations between H+ density and the ion temperature are positive in most of the latitudes except for serval degrees around 9°N. The latitudinal variations in the correlation coefficients lead us to suggest that thermal conduction is likely more important than ion-neutral collision in the ion energy budget at 600 km. Additionally, semiannual oscillations with peak amplitudes in winters and summers at the extra-equatorial latitudes are revealed in the observations of diurnal migrating tides in the topside ionosphere, which are different from the latitudinal and seasonal distributions of diurnal migrating tides captured in the lower thermospheric temperature and total electron content.